Metabolomics of fecal samples: A practical consideration. (November 2016) - Matysik, Silke; Le Roy, Caroline Ivanne; Liebisch, Gerhard; Claus, Sandrine Paule
Abstract: Background: Metabolic profiling is becoming increasingly popular to identify subtle metabolic variations induced by diet alterations and to characterize the metabolic impact of variations of the gut microbiota. In this context, fecal samples, that contain unabsorbed metabolites, offer a direct access to the outcome of diet – gut microbiota metabolic interactions. Hence, they are a useful addition to measure the ensemble of endogenous and microbial metabolites, also referred to as the hyperbolome. Scope and approach: Many reviews have focused on the metabolomics analysis of urine, plasma and tissue biopsies; yet the analysis of fecal samples presents some challenges that have received little attention. We propose here a short review of current practices and some practical considerations when analyzing fecal material using metabolic profiling of small polar molecules and lipidomics. Key findings and conclusions: To allow for a complete coverage of the fecal metabolome, it is recommended to use a combination of analytical techniques that will measure both hydrophilic and hydrophobic metabolites. A clear set of guidelines to collect, prepare and analyze fecal material is urgently needed. Highlights: Untargeted metabolic profiling of fecal material is robustly achieved using NMR-based metabolomics. Mass spectrometry mostly used for targeted metabolic profiling of a class of molecules for deep coverage and high sensitivity. Lipidomics profiles contain endogenous, diet-related and microbial lipids that may be of potential interest for bacterial identification.